Identification of serum and tissue micro‐RNA expression profiles in different stages of inflammatory bowel disease. (4th July 2013) - Iborra, M.; Bernuzzi, F.; Correale, C.; Vetrano, S.; Fiorino, G.; Beltrán, B.; Marabita, F.; Locati, M.; Spinelli, A.; Nos, P.; Invernizzi, P.; Danese, S.
Summary The altered expression of micro‐RNA (miRNA) has been associated with Crohn's disease (CD) and ulcerative colitis (UC). The aim of this study was to establish specific miRNA expression patterns in the serum and mucosa of inflammatory bowel disease (IBD) patients (UC and CD with colonic involvement) at different stages of the disease. Serum and biopsies from nine active CD (aCD), nine inactive CD (iCD), nine active UC (aUC) and nine inactive UC (iUC) and serum from 33 healthy subjects were collected. Up to 700 miRNAs were evaluated by the TaqMan® human miRNA array. The ΔCt values were obtained using the mean expression values of all expressed miRNAs in a given sample as a normalization factor for miRNA real‐time quantitative polymerase chain reaction data. The levels of serum miRNAs in CD and UC patients were different to healthy subjects. Thirteen serum miRNAs were expressed commonly in CD and UC patients. Two miRNAs were higher and four miRNAs were lower in the serum of aCD than iCD. No serum miRNA was regulated exclusively in aUC compared with iUC patients. Four miRNAs were higher and three miRNAs were lower in the mucosa of aCD than iCD. Two miRNAs were higher and three miRNAs were lower in the mucosa of aUC than iUC. No serum miRNAs coincided with tissue miRNAs in aCD and aUC patients. Our results suggest the existence of specific miRNA expression patterns associated with IBD and their different stages and support the utility of miRNA as possible biomarkers. This pilot study needs to be validated in a large prospective cohort.